Does Household Food Insecurity Affect the Nutritional Status of Preschool Children Aged 6–36 Months?. (1st July 2013) - Saaka, Mahama; Osman, Shaibu Mohammed
Abstract : Introduction . This study used three dependent measures of food security to assess the magnitude of household food insecurity and its consequences on the nutritional status of children 6–36 months in Tamale Metropolis of Northern Ghana. Methods . An analytical cross-sectional study was conducted on a sample of 337 mother/child pairs in June 2012. Food access was measured as household food insecurity access scale (HFIAS), household dietary diversity score (HDDS), and food consumption score (FCS). Results . The magnitude of household food insecurity depended on the food access indicator, with HFIAS yielding the highest household food insecurity of 54%. Of the three food access indicators, 30-day HFIAS was not related to any of the nutrition indices measured. HDDS and FCS were both significantly associated with BMI of mothers and chronic malnutrition (stunted growth) but not acute malnutrition (wasting) with FCS being a stronger predictor of nutritional status. Compared to children in food insecure households, children in food secure households were 46% protected from chronic malnutrition (O R = 0.54, 95% CI: 0.31–0.94). Conclusions and Recommendations . The results of this study show that different measures of household food insecurity produce varied degree of the problem. Efforts at reducing chronic child malnutrition should focus on improving the adequacy of the diet.